Computed tomography with a full FOV photon-counting detector in a clinical setting, the first experience. Issue 137 (April 2021) - Ferda, Jiří; Vendiš, Tomáš; Flohr, Thomas; Schmidt, Bernhard; Henning, André; Ulzheimer, Stefan; Pecen, Ladislav; Ferdová, Eva; Baxa, Jan; Mírka, Hynek
Highlights: Photon-counting CT detector system reduced electronic noise and its impact on image quality. The smallest pixel size of 0.2 mm enables more detailed high resolution imaging of small airways and submillimeter arteries. Photon-counting detector is able to discriminate photons of different energies, thus the direct spectral analysis provides monochromatic CT images in several energy levels. Abstract: Objectives: to assess the feasibility of CT with an integrated photon-counting-detector system (PC-CT) in the body imaging of clinical patients. Methods: 120 examinations using photon counting detector CT were evaluated in six groups: 1/ a standard-dose lung, 2/ low-dose lung, 3/ ultra-high resolution (UHR) lung, 4/ standard-dose abdominal, 5/ lower-dose abdominal, 6/ UHR abdominal CTA. All CT examinations were performed on a single-source prototype device equipped with a photon counting detector covering a 50 cm scan field of view. Standard dose examinations were performed with the use of detector element size of 0.4 mm, ultra-high-resolution examinations with the detector element size of 0.2 mm, respectively. The stability of the system during imaging was tested. The diagnostic quality of the acquired images was assessed based on the imaging of key structures and the noise level in five-point scale, the effective dose equivalent, dose length product and noise level, and also relation to body mass index and body surface area were compared with three similar groups of CT images made with energy integrating high end scanner. The parameters were evaluated using Wilcoxon test for independent samples, the independence was tested using Kruskal-Wallis test. Results: When PC-CT images radiation dose is compared with the similar imaging using energy integrating CT, the PC-CT shows lower dose in ultra-high resolution mode, the dose is significantly lower (p < 0.0001), the standard dose examinations were performed with the comparable radiation doses. PC-CT exhibited the significantly higher ratio between parenchyma signal and background noise both in lung and in abdominal imaging (p < 0.0001). Conclusions: PC-CT showed imaging stability and excellent diagnostic quality at dose values that are comparable or better to the quality of energy integrating CT, the better signal and improved resolution is most important advantage of photon counting detector CT over energy integrating detector CT.